2020
DOI: 10.1111/geb.13148
|View full text |Cite
|
Sign up to set email alerts
|

Current climate, but also long‐term climate changes and human impacts, determine the geographic distribution of European mammal diversity

Abstract: Aim Historical climate variations, current climate and human impacts are known to influence current species richness, but their effects on phylogenetic and trait diversity have been seldom studied. We investigated the relationship of these three factors with the independent variations of species, phylogenetic and trait diversity of European mammals. Considering the position of the 0 ºC isotherm in the Last Glacial Maximum as a tipping point, we tested the following hypotheses: northern European assemblages hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 89 publications
2
20
0
Order By: Relevance
“…However, although the climatic characteristics within the PAs did not differ significantly from the regions where they are located (see Supplementary Appendix 2 in Data Sheet 1), our results showed that both diversity facets were influenced by the climatic conditions found within the PA's boundaries. These results agree with the findings of Santos et al (2020), who concluded that current climate strongly affects both functional and phylogenetic diversity gradients of European mammals. Particularly, we found a tendency for higher functional and phylogenetic diversity than expected from the regional pool in PAs with high annual precipitations and low annual mean temperature.…”
Section: Predictorsupporting
confidence: 93%
See 3 more Smart Citations
“…However, although the climatic characteristics within the PAs did not differ significantly from the regions where they are located (see Supplementary Appendix 2 in Data Sheet 1), our results showed that both diversity facets were influenced by the climatic conditions found within the PA's boundaries. These results agree with the findings of Santos et al (2020), who concluded that current climate strongly affects both functional and phylogenetic diversity gradients of European mammals. Particularly, we found a tendency for higher functional and phylogenetic diversity than expected from the regional pool in PAs with high annual precipitations and low annual mean temperature.…”
Section: Predictorsupporting
confidence: 93%
“…and Dufour, 2007). This methodology has been widely used in the literature in studies including similar goals to ours (e.g., Roa-Fuentes et al, 2019;Santos et al, 2020). Then, the Iberian functional dendrogram of each tetrapod group was pruned to each regional pool (composed by the species observed in each PA and respective buffer zone).…”
Section: Diversity Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the fit of the initial a priori model was not good; according to the guidance of modification indices (MIs), we respecified the model by adding new relationships. We sequentially added new relationships with biological meaning until an adequate model fit was achieved (Santos et al, 2020). After fitting the final model, we tested the goodness of fit of the models by means of maximum-likelihood estimation on the variance-covariance matrix.…”
Section: Response Of Wild Boars' Nest Site Selection To Anthropogenic...mentioning
confidence: 99%